Social Work and Environmentally Induced Displacement: A Commentary - Drolet, Julie; Sampson, Tiffany; Jebaraj, Deborah Prashanthi; Richard, Laura (Refuge: Canada's Journal on Refugees, 2014)
Environmentally induced displacement is a growing concern across the globe. The human and social dimensions of affected displaced and migrating populations are of concern to the profession of social work, as many social workers are directly involved in working with vulnerable populations affected by environmental changes due to climate change, disasters, and environmental degradation. This new reality presents challenges in addressing social and economic inequalities and disparities, and this commentary argues for a need to build capacity among practitioners to consider the interconnections of social, economic, and environmental challenges in bridging practice and policy in ongoing legal discourses.